HANDLING OF SPATIO-TEMPORAL PATTERN QUERIES IN MOVING OBJECT DATABASE - Fauzul Yogiandra, Ahmad
Moving object database is a collection of geometric data that changing over time. The existence of a moving object database allows database users to express a series of predicates that state the events or the changes that happened during the movement of a moving object. The class of queries that involves a series of predicates is called Spatio-temporal pattern (STP) queries. STP query has temporal order constraints on the fulfillment of predicates involved. The implementation of the STP query is unavailable on existing database management systems (DBMS). Developing a tool to express the STP query needs to be done. This is to allow any kind of questions that could not be asked before. STP query is expressed using the STP predicate which has a design consisting of two parts. The first defines lifted predicates that accept moving object arguments and report the time intervals, during which they are fulfilled. The second part is to define temporal constraints on the predicate fulfillments. Temporal constraints are defined as temporal relationships between pairs of time intervals. Implementation of STP queries is done by providing data structures for moving objects, methods for evaluating operations on moving objects, and functions for defining STP predicates. The implementation is collected into a single package called extension. Extension is a form of tool built on the DBMS to handles STP queries in a moving object database. The extension is built on PostgreSQL which provides spatial data types and operations through PostGIS. The testing of the tool is done by executing several STP queries. The test results show that the tool built successfully handles STP queries in a moving object database.